2018
DOI: 10.1021/acsomega.8b02844
|View full text |Cite
|
Sign up to set email alerts
|

Alkali Metal Ion Storage of Quinone Molecules Grafted on Single-Walled Carbon Nanotubes at Low Temperature

Abstract: 9,10-Anthraquinone and 9,10-phenanthrenequinone (PhQ) were grafted onto two kinds of single-walled carbon nanotube (SWCNT) samples having different mean tube diameters by diazo-coupling reactions. The structural details of PhQ-grafted SWCNT (PhQ/SWCNT) samples were analyzed by X-ray diffraction and Raman measurements. It was discussed that a few-nanometer-thick layer of polymerized PhQs covers the outside of SWCNT bundles. The obtained PhQ/SWCNT works very well as lithium-ion battery and sodium-ion battery ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Similarly, 9,10-phenanthrenequinone (PhQ) has also been grafted onto the single-walled carbon nanotube (SWCNT) sample by a diazo-coupling reaction. Moreover, the obtained PhQ-grafted SWCNTs as LIB and SIB electrodes present excellent electrochemical performances at low temperature (0 °C) . Via a multistep grafting technique, a quinone compound, 2,3-dicyano- p -benzoquinone (DCBQ), has been successfully functionalized onto the carbon nanotubes (CNTs) (Figure e) .…”
Section: Redox-active Feature For Electrodementioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, 9,10-phenanthrenequinone (PhQ) has also been grafted onto the single-walled carbon nanotube (SWCNT) sample by a diazo-coupling reaction. Moreover, the obtained PhQ-grafted SWCNTs as LIB and SIB electrodes present excellent electrochemical performances at low temperature (0 °C) . Via a multistep grafting technique, a quinone compound, 2,3-dicyano- p -benzoquinone (DCBQ), has been successfully functionalized onto the carbon nanotubes (CNTs) (Figure e) .…”
Section: Redox-active Feature For Electrodementioning
confidence: 98%
“…Moreover, the obtained PhQ-grafted SWCNTs as LIB and SIB electrodes present excellent electrochemical performances at low temperature (0 °C). 179 Via a multistep grafting technique, a quinone compound, 2,3-dicyano-p-benzoquinone (DCBQ), has been successfully functionalized onto the carbon nanotubes (CNTs) (Figure 7e). 180 As shown in Figure 7f and Figure 7g, resulting from the excellent redox activity, the CNTs-DCBQ electrode exhibits the most outstanding electrochemical properties among the CNT-based materials in LIBs, delivering a large reversible capacity of 170 mAh g −1 based on the total weight of the electrode loading.…”
Section: Carbon Materials Withmentioning
confidence: 99%
“…To date, a number of strategies have been explored to suppress the dissolution of organic small molecule materials, including the introduction of metal ions to form coordination bonds between molecules (salt formation), [ 14 ] the polymerization of the small molecules, [ 15 ] the immobilization through carbonaceous host materials, [ 16 ] and employment of surface coating. [ 17,18 ] However, the long‐cycle performance was still unsatisfactory even when the above strategies were employed.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, unexpectedly weak reduction processes and negligible electron mobility were observed depriving the desired study of the resulting copolymer. Our attention then turned to nanotube dispersion as recent reports have demonstrated that interactions between redox organic molecules and carbon nanotubes can increase the conductivity of the organic materials. ,, It can also facilitate redox reactions by π–π interactions with the nanotubes in addition to overcoming the inherent dissolution problem. In this study, single-walled carbon nanotubes (SWCNTs) were dispersed with the copolymer using the conjugated polymer-assisted dispersion method . High concentration dispersion was filtered to obtain a freestanding film that was used directly as a cathode.…”
Section: Introductionmentioning
confidence: 99%